If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22x + 23 + -17x + -16 = x + -8 + 2x + 27 Reorder the terms: 23 + -16 + 22x + -17x = x + -8 + 2x + 27 Combine like terms: 23 + -16 = 7 7 + 22x + -17x = x + -8 + 2x + 27 Combine like terms: 22x + -17x = 5x 7 + 5x = x + -8 + 2x + 27 Reorder the terms: 7 + 5x = -8 + 27 + x + 2x Combine like terms: -8 + 27 = 19 7 + 5x = 19 + x + 2x Combine like terms: x + 2x = 3x 7 + 5x = 19 + 3x Solving 7 + 5x = 19 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 7 + 5x + -3x = 19 + 3x + -3x Combine like terms: 5x + -3x = 2x 7 + 2x = 19 + 3x + -3x Combine like terms: 3x + -3x = 0 7 + 2x = 19 + 0 7 + 2x = 19 Add '-7' to each side of the equation. 7 + -7 + 2x = 19 + -7 Combine like terms: 7 + -7 = 0 0 + 2x = 19 + -7 2x = 19 + -7 Combine like terms: 19 + -7 = 12 2x = 12 Divide each side by '2'. x = 6 Simplifying x = 6
| X(1+x)(3-x)=3 | | (x^2d^2-3xd+4)y=x+x^2*lnx | | (x+5)*(x+5)=1280 | | 8-p=1 | | n^3-3n^2+2n-60=0 | | (x+5)*(x+5)*(x+5)=1280 | | 18x+15-15x+26=-4+7+9x+6 | | 12-3(-4-2y)=-5 | | 18x+15+15x+26=-4+7+9x+6 | | 6-5=2 | | 5+8i=0 | | y=tan(6x) | | 12+13=x | | -7-13z+15+16z=57-5z+4z-52 | | (2x-1)(3x-2)=33 | | 3x+14+6x-29=43+8x-70-32 | | 3x+14+6x-29=m-3+4m-4 | | 12m+6n-6m+10n= | | 10m+12-4m-19=m-3+4m-4 | | (3x+y^2+2y^5)dx+(2x^2y+5xy^4)dy=0 | | x^2-12i=5 | | 7+9d-4-4d=5d+3-d+8 | | 10x-5+2=7x+21 | | -2(2x+3)-4=-7 | | 5j*6y= | | 3x+y-15=0 | | 4y+5y=6 | | -8t+16=7(10-8t) | | 10+3x-2+x=3x+6+2x+8 | | -15-2(-3y+5)=10 | | 5x+8-3x-11=3x-5 | | 4(3t-2)=5(2t+3) |